Methodological Considerations in Social Cost Studies of Addictive Substances: A Systematic Literature Review - Verhaeghe, Nick; Lievens, Delfine; Annemans, Lieven; Vander Laenen, Freya; Putman, Koen (Frontiers in Public Health, 2017)
Background: Alcohol, tobacco, illicit drugs and psychoactive pharmaceuticals’ use is associated with a higher likelihood of developing several diseases and injuries and as a consequence considerable health care expenditures. There is a yet a lack of consistent methodologies to estimate the economic impact of addictive substances to society. The aim was to assess the methodological approaches applied in social cost studies estimating the economic impact of alcohol, tobacco, illicit drugs and psychoactive pharmaceuticals. Methods: A systematic literature review through the electronic databases Medline (Pubmed) and Web of Science was performed. Studies in English published from 1997 examining the social costs of the addictive substances alcohol, tobacco, illicit drugs and psychoactive pharmaceuticals were eligible for inclusion. Results: Twelve social cost studies met the inclusion criteria. In all studies, the direct and indirect costs were measured, but the intangible costs were seldom taken into account. A wide variety in cost items included across studies was observed. Sensitivity analyses to address the uncertainty around certain cost estimates were conducted in eight studies considered in the review. Conclusion: Differences in cost items included in cost-of-illness studies limit the comparison across studies. It is clear that it is difficult to deal with all consequences of substance use in cost-of-illness studies. Future social cost studies should be based on sound methodological principles in order to result in more reliable cost estimates of the economic burden of substance use.